1985
DOI: 10.1108/eb045997
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, Solder Thickness and Solder Alloy Effects on Circuit Board Solderability

Abstract: The paper presents the results of extensive studies on circuit board solderability comparing wetting balance and IPC test methods through performance in vapour phase and wave soldering operations. The effects on solderability of key parameters are examined and compared with storage times of one year, and accelerated ageing using damp heat, dry heat and steam oxygen. An evaluation is made of tin‐lead alloys from 40/60 to 70/30 in solder coating thicknesses from 0·1 to 1·0 mil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…However, the number of defects per board ranged from 0 to 6, not substantially higher than the 0 -2 defects observed for the untreated boards. Consistent with this, an earlier study [Hagge and Davis 1985] found that circuit boards steam aged for 4 hours exhibited fewer soldering defects than typical production boards. A reasonable explanation for the good performance observed is that the very thick oxides produced by steam aging can crack during wave soldering and be removed as scale, allowing the underlying solder coating to melt.…”
Section: Oxides Produced By Steam Agingsupporting
confidence: 57%
See 1 more Smart Citation
“…However, the number of defects per board ranged from 0 to 6, not substantially higher than the 0 -2 defects observed for the untreated boards. Consistent with this, an earlier study [Hagge and Davis 1985] found that circuit boards steam aged for 4 hours exhibited fewer soldering defects than typical production boards. A reasonable explanation for the good performance observed is that the very thick oxides produced by steam aging can crack during wave soldering and be removed as scale, allowing the underlying solder coating to melt.…”
Section: Oxides Produced By Steam Agingsupporting
confidence: 57%
“…Although many workers have relied heavily on subjective dip-and-look solderability tests and have not adequately controlled the oxygen content during steam aging, there is nonetheless general agreement on several important points. Solderability degradation occurs much more rapidly in the presence of water vapor, for both artificial [Edington and Lawrence 1988;Steen and Bengston 1987;Geist 1983] and natural aging [Stoneman and MacKay 1977], and is most severe for the steam aging procedure [Edington and Lawrence 1988;Hagge and Davis 1985]. Insufficient coating thickness has consistently been found to be the most important factor leading to solderability loss.…”
Section: Accelerated Aging Proceduresmentioning
confidence: 99%
“…[1][2][3][4][5] During the life time of the products, thermal excursion and shocks are encountered. Failures due to aging can occur in field use and are often the result of intermetallic compound (IMC) growth.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, signifi-cant reactivity occurs even below the melting temperature of the solder, as was shown by Walker and De-Haven (1984). These reactions between the solder and metallization form intermetallic phases, which are generally detrimental to solder wetting (Hagge and Davis, 1984;Klein Wassink, 1989;Walker and De-Haven, 1984) and may be responsible for dewetting behavior by consuming the Au reactant necessary for the wetting reaction to continue. Likewise, substantial premelting reaction will alter the subsequent flow behavior in that amounts of reactants and high-reactivity paths are diminished.…”
Section: Discussionmentioning
confidence: 99%